Leiomyosarcoma of Pulmonary Vein Presenting as Left Atrial Mass: An Outline of Management Principles - Philemon Gukop; Guido Frassetto; Georgios Karapanagiotidis; Venkatachalam Chandrasekaran (Case Reports in Cardiology)
Leiomyosarcoma of the pulmonary vein is rare and has poor prognosis. Its clinical features are nonspecific and mimic benign conditions. Early diagnosis is challenging. Most cases have been diagnosed only at autopsy or on postoperative histology specimens. Treatment is essentially palliative complete surgical excision. We outline the principles of management with the case of a 39-year-old man with leiomyosarcoma of the left pulmonary veins extending into the left atrium. Extensive investigation to achieve early diagnosis and determine extent of disease is essential. Frozen section guided adequate excision of all cardiac tumours and resection of involved lung tissue achieve local disease control. Adjuvant chemoradiotherapy has been shown to enhance survival.